Interprofessional training for the delivery of community health services in Mexico: the experience of Partners in Health. Issue 4 (4th July 2019) - Nigenda, G.; Elliott, P.; Flores, H.; Aristizabal, P.; Martinez-Davalos, A.
ABSTRACT: Interprofessional training in health is scarce in Mexico. Partners in Health (CES in Spanish), is the branch of an international civil society organization that provides health services to poor and rural populations. CES runs a set of ten health centers in Chiapas, Mexico, in partnership with the local Ministry of Health. A key component of the provision strategy is to train healthcare providers, mainly medical and nursing students in their final year of training, to create healthcare teams that work together while fostering their individual capacities. CES offers a diploma on Global Health and Social Medicine, where medical and nursing students -also called pasantes- interact to discuss jointly the effects of global and social determinants of health in local communities, as well as specific clinical topics. A qualitative study including interviews and nonparticipant observations was undertaken to identify initial achievements and challenges of the experience. CES has achieved important benefits related to teamwork as well as clinical capacities of individuals as healthcare providers. However, challenges have emerged: differences in social origin, personal development expectations, professional identity and institutional roles hinder team cohesion. Consequently, CES has introduced adjustments to reduce the negative impact of these differences. Although the training model needs further development, the possibility of transferring some of its good practices to non-CES scenarios should be seriously considered by health authorities.